FINANCIAL INFORMATION VS. NON-FINANCIAL INFORMATION, A REFLECTION OF MARKET PERCEPTION - Diky Darmawan; Novita; Imam Nurcahyo Fambudi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This study examines the impact of Environmental, Social, and Governance (ESG) disclosure and profitability on business value, with Chief Executive Officer (CEO) tenure operating as a moderating variable. This research examines the growing significance of sustainability reporting and economic prosperity in Indonesia's consumer cyclicals industry, emphasizing the underexplored impact of CEO tenure on the relationship between ESG disclosure and firm value. Utilizing a quantitative methodology and random effect model, the study analyzes a sample of consumer cyclicals companies listed on the Indonesia Stock Exchange from 2019 to 2021. The findings indicate that both ESG disclosure and profitability have a positive and significant impact on firm value, and CEO tenure strengthens the relationship between ESG disclosure and firm value. These results underscore the critical role of sustainability practices, financial performance, and experienced leadership in improving firm value, providing meaningful implications for corporate governance and stakeholder decision-making. The implication of this study is that PJOK 51/2017 helps companies understand ESG reporting obligations and encourages increased financial transparency